Soziale Arbeit und die Soziale Frage - Fontanellaz, Barbara; Reutlinger, Christian; Stiehler, Steve (Seismo, 2018)
"For a long time, the use of the term «Social Question» was referred to as being a phenomenon of the 19th century, related to the social changes taking place during that period. Today, however, the so-called Social Question is increasingly linked to current societal challenges, such as global migration, radical demographic change, or increased social divisions in both public and professional debates. In the light of the above, the present volume approaches the complexity of social issues and social work, whereby contributions with a historical, theoretical, phenomenological or political focus stand side by side, in both complementary or contradictory ways. The main purpose is to create references to actuality and to identify potentials for development which should help to deal with the historical meaning of the Social Question as well as to recontextualize the latter in our time."